Role of Defect Type in Optimizing Photoelectrochemical Hydrogen Production Catalysts - Mahrous, Mohamed (AUC Knowledge Fountain, 2023)
The search for new energy sources has become a global challenge due to the increasing demand for energy and the negative impact of traditional energy sources on the environment. The photoelectrochemical water splitting has emerged as a promising alternative source for producing hydrogen, which can be used as a clean fuel. However, it is necessary to tailor the properties of the light-active material that will be used to absorb sunlight and split water. This research project aimed at providing detailed insights into the effect of varying the type and concentration of defects on the optical and electronic properties of diamond as a catalyst for photoelectrochemical water splitting. This study focused on three categories of dopants, including one, two, and three substituted boron atoms, as well as additional substitution dopants, such as nitrogen. The selection of boron and nitrogen dopants was based on their rich p- and ncharacteristics, respectively, which could enhance the catalytic properties of the material. Interstitial hydrogen atoms were also introduced as another type of defect to stress the lattice atoms and cause variations in the electronic and optical properties of the material. The results showed that the type and concentration of dopants is significantly affecting the band gap, dielectric constant, and absorption of the material. The band gap decreased with increasing the concentration of dopants, indicating that higher dopant concentrations enhanced the ability of the material to conduct electricity. The dielectric constant and absorption coefficient also showed a strong dependence on the type and concentration of dopants. For example, the addition of interstitial hydrogen atoms caused a significant reduction in the dielectric constant, while the addition of nitrogen dopants increased the absorption coefficient of the material. The study also applied the conclusions drawn from the analysis to another material, CuO, and found that the material exhibited the expected behavior. This finding indicates that the conclusions drawn from the analysis of the first material are generally applicable to other materials.